Review of the genus Habropogon Loew, 1847 (Diptera: Asilidae) from Russia, with description of new species from Siberia - Sakhvon, Vital V.; Lelej, Arkady S. (Zootaxa, 2017)
Five species of genus Habropogon Loew, 1847 from Russia are reviewed. Habropogon lehri Sakhvon sp. nov. (Altai Republic and Zabaykalsky Territory) is described and illustrated. The status of H. verticalis mesasiaticus Lehr, 1960 is updated to species level and a lectotype of the latter is designated. Habropogon mesasiaticus Lehr is newly recorded from Russia, Turkmenistan and Uzbekistan. A key to males of the species is presented.